Halal tourism sector and tax allowance policy: a case study observed from normative problems to effective implementation - Abdul Kadir Jaelani; Resti Dian Luthviati; Muhammad Jihadul Hayat; Abdur Rohim (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
Various tax allowance policies have been established by the government to revive the Indonesian tourism sector. However, it is crucial to examine whether the tax allowance policy can enhance the tax and tourism revenue in the halal tourism sector in West Nusa Tenggara. This research aims to provide a prescription for the Tax Allowance Policy in West Nusa Tenggara by employing a normative legal study with a statute approach and conceptual approach. This research suggests that the tax allowance policy has not effectively contributed to the recovery of the halal tourism sector in West Nusa Tenggara. The factors contributing to the situation include the disharmony between policies promoting halal tourism and the provisions outlined in Article 18B, paragraph (5) of the 1945 Constitution of the Republic of Indonesia and the principles of "Bhinneka Tunggal Ika" (Unity in Diversity). In addition, this disharmonious Tourism Policy has resulted in a rise in the poverty levels in West Nusa Tenggara, thereby designating it as Indonesia’s poorest region. In practical terms, the finding of this research serves as a theoretical basis for the government to implement tax allowance policies to aid in the recovery and development of the halal tourism sector. This includes considerations for both legal substance and legal structure. For instance, in terms of substance, this guidance offers directives for local regulations, focusing on attribution and delegation, fostering equal business opportunities and benefits, as well as enabling the adaptation to challenges arising from local, national, and global changes.